A randomized clinical trial on anterior approach vs conventional hepatectomy for resection of colorectal liver metastasis: to terminate or not to terminate the study : in reply - Rahbari, Nuh Nabi; Birgin, Emrullah; Weitz, Jürgen (JAMA surgery, 2021)
In Reply We would like to thank Gupta and colleagues for their comments on our article and for the opportunity to clarify the issues they mentioned. They correctly noted that the study was terminated prematurely despite a reported P value of .54 in the interim analysis, which is less than the P value of .65 required in the study protocol. In the study protocol, we planned to test the primary end point in the interim analysis using a 2-sided Fisher exact test. Unfortunately, we reported the results of the 1-sided Fisher exact test in our article. However, the 2-sided Fisher exact test yields a P value of more than .99, which justifies premature termination of the trial after the interim analysis. Further, Gupta et al noted that the number of patients displayed in the Kaplan-Meier plot on overall survival lacks 1 patient in the anterior approach arm (ie, n = 38 instead of n = 39). We apologize for this error. However, the error only applies to the number of patients displayed on the bottom of the Kaplan-Meier plot (ie, the number of patients at risk). The log-rank test was performed on all patients (ie, n = 41 vs n = 39 patients). Therefore, the reported results are correct. The authors suggested further analyses of overall survival and disease-free survival based on the intraoperative circulating tumor cells. As the number of intraoperative circulating tumor cells detection was rather low in the total cohort (n = 11), further meaningful stratification and subgrouping in this cohort was not possible. Finally, Gupta et al highlighted that based on the results of our randomized trial, “both approaches may offer comparable, but not equivalent, survival outcomes because the clinical trial was not designed as a noninferiority study.” We fully agree with them and therefore in our article concluded that the anterior approach was not superior to conventional hepatectomy without using the term equivalent.
Gesehen am 02.02.2023